Penerapan Metode Case-Based Reasoning pada Website SORTING (Sorong Atasi Stunting) Sebagai Implementasi Smart City (Studi Kasus: Distrik Sorong Timur) - Manuhutu, Melda; Tindage, Jalmijn; Bobii, Permenas (Diponegoro University, 2024)
Stunting is one of the issues designated as a national priority issue at this time. Determining this priority issue is to accelerate the level of achievement of national development goals. East Sorong District, Sorong City, Southwest Papua Province is one of the focus location with a high prevalence rate. This study aims to develop an information technology called SORTING (Sorong Atasi Stunting) using the case-based reasoning method. This research produces a system that can be accessed from anywhere and at any time, which can be used by residents, especially mothers, to consult regarding their baby's growth problems. SORTING was developed using the expertise of nutritionists who usually deal with stunting problems. SORTING resulted in several conclusions that the application expert system can diagnose stunting by using the case-based reasoning method as an engineering approach to the knowledge base; The application of the SORTING expert system can provide an overview of stunting including the results of the percentage of diagnoses, factors and recommendations for solutions that must be taken; The application of the SORTING expert system can be used as a second alternative to consult with experts in diagnosing stunting. And it can also be an alarm to continue consulting with experts directly; The application of the SORTING expert system can increase knowledge about stunting. The researchers hope that SORTING can assist the government in the National Action Plan for Stunting Management which emphasizes reducing stunting rates and can help the community recognize stunting diseases early and prevent them.